Deteksi Kualitas Kuning Telur Ayam Kampung Menggunakan Ekstraksi Ciri Secara Statistika Orde Satu Berbasis Logika Fuzzy - Sipan, Muhammad; Pramuyanti, Rony Kartika (Universitas Semarang, 2020)
Chicken eggs have become a basic necessity for Indonesians, both for personal consumption and for business purposes. Eggs that are good or quality can be seen based on the yolk. Both those who are only a day old a week or more than two weeks or those that are not suitable for consumption.Quality egg yolks appear brighter in yellow and there are no stripes or other colors and markings in the yolk. Eggs. From this, the author tries to do research on the detection of quality detection of native chicken egg yolk using Order One Statistical Extraction based on Fuzzy Logic. Feature extraction The first order egg yolk image in this study uses various features, namely variance, skewness, cartulation, entropy and mean. Texture measurements in the first order use statistical calculations based on the original image pixel value for the sole purpose of finding the histogram characteristics of the image.The results of this study are the value of the feature calculation in first order statistics to be used to make the decision whether the egg yolk is suitable for consumption or not. This research is expected to be able to provide insight in determining the quality or absence of native chicken eggs. The first step in this research is to look for data in the form of egg yolks from native chickens, after that we take a picture in the form of an image of egg yolk using the same camera and the same distance as well. So that the image results obtained have the same level of precision. From this image, we then look for the first order statistical value which will be used as a reference in determining the quality of eggs using fuzzy logic.